Search for excited quarks in the γ+jet final state in proton–proton collisions at s=8 TeV - V. Khachatryan; A.M. Sirunyan; A. Tumasyan; W. Adam; T. Bergauer; M. Dragicevic; J. Erö; C. Fabjan; M. Friedl; R. Frühwirth; V.M. Ghete; C. Hartl; et al. (Physics Letters B, 2014)
A search for excited quarks decaying into the γ+jet final state is presented. The analysis is based on data corresponding to an integrated luminosity of 19.7 fb−1 collected by the CMS experiment in proton–proton collisions at s=8 TeV at the LHC. Events with photons and jets with high transverse momenta are selected and the γ+jet invariant mass distribution is studied to search for a resonance peak. The 95% confidence level upper limits on the product of cross section and branching fraction are evaluated as a function of the excited quark mass. Limits on excited quarks are presented as a function of their mass and coupling strength; masses below 3.5 TeV are excluded at 95% confidence level for unit couplings to their standard model partners. Keywords: CMS, Physics, Photon, Jet